LOGARITHMIC FUNCTIONS, EQUATIONS AND INEQUALITIES - Abdullayev Nurbek Shuhrat o'g'li; Ro'ziqulov Sa'dulla Egamnazar o'g'li (American Journals, 2025)
This article provides information on logarithmic functions, equations, and solutions to inequalities.
Keywords: Logarithmic functions, equations, inequalities, graph, function, interval positive.